Rapid thermal annealing of CH3NH3PbI3 perovskite thin films by intense pulsed light with aid of diiodomethane additive. Issue 20 (8th May 2018) - Ankireddy, Krishnamraju; Ghahremani, Amir H.; Martin, Blake; Gupta, Gautam; Druffel, Thad
Abstract : Perovskite thin films are thermally annealed using a rapid intense pulsed light technique enabled by an alkyl halide that collectively improves device performance when processed in ambient conditions. Abstract : The organic metal halide perovskite material is capable of high throughput manufacturing via traditional deposition processes used in roll-to-roll, yet thermal annealing post deposition may require long ovens. We report rapid annealed perovskite thin films using intense pulsed light (IPL) to initiate a radiative thermal response that is enabled by an alkyl halide additive that collectively improves the performance of a device processed in an ambient environment from a baseline of 10 to 16.5% efficiency. Previous reports on CH3 NH3 PbI3 perovskite films using IPL processing achieved functional devices in milli-second time scales and are promising for high throughput manufacturing processes under ambient conditions. In this study, we found that the addition of diiodomethane (CH2 I2 ) as an additive to the methylammonium iodide (MAI)/lead iodide (PbI2 ) precursor ink chemistry and subsequent IPL thermal annealing are inter-dependent. The concentration of CH2 I2 and IPL processing parameters have a direct effect on the surface morphology of the films and performance within a perovskite solar cell (PSC). The CH2 I2 dissociates under exposure to ultraviolet (UV) radiation from the IPL source liberating iodine ions in the film, influencing the perovskite formation and reducing the defect states. We anticipate that these results can be utilized to further develop different ink formulations using alkyl halides for the IPL technique to improve the performance of perovskite solar cells processed in ambient conditions.